Aryl substituted 2, 6-di(thiazol-2-yl)pyridines –excited-state characterization and potential for OLEDs. (October 2019) - Choroba, Katarzyna; Kula, Sławomir; Maroń, Anna; Machura, Barbara; Małecki, Jan; Szłapa-Kula, Agata; Siwy, Mariola; Grzelak, Justyna; Maćkowski, Sebastian; Schab-Balcerzak, Ewa
Abstract: A series of 2, 6-di(thiazol-2-yl)pyridines ( dtpy ) functionalized at 4-position with 1-naphtyl (1 ), 2-naphtyl (2 ), 9-anthryl (3 ), 2-anthryl (4 ), 9-phenantryl (5 ) and 1-pyrenyl (6 ) groups has been synthesized and thoroughly investigated. The molecular formulas of 1 –6 were determined by 1 H and 13 C NMR, elemental analysis and X-Ray analysis (1, 3 and 5 ). In the solid state structures, the dtpy framework shows good planarity, while the aryl substituent is significantly inclined to the central pyridine to minimize inter-ring H⋯H repulsions and hydrogen–π-ring steric repulsions. The nature of excited states involved in the photophysical processes has been explored by carrying out absorption and emission UV–Vis studies in solution and solid state, as well as quantum chemical calculations. Large aryl substituents, such as anthryl and pyrenyl, induce a remarkable red-shift of the absorption and emission bands, in agreement with a stronger π-delocalization. For compounds 3, 4 and 6, which show a large, positive solvatochromism, the excited states gain significant charge transfer (CT) character. The efficiency of the ICT/TICT state formation was found to depend on solvent polarity and torsional hindrance between the aryl and dtpy moieties. To investigate the impact of torsional hindrance on ICT formation, ultrafast pump–probe measurements were performed for compounds 3 and 4 . All the synthesized dtpy were electrochemically active and undergo oxidation and reduction processes, as was revealed by CV and DPV measurements. The particular choice of aryl substituent significantly impacts the thermal properties and electroluminescence ability of the investigated 2, 6-di(thiazol-2-yl)pyridines. Graphical abstract: Image 1 Highlights: The dtpy substituted by aryl groups have been synthesized and characterized as D-A. The aryl substituents give lowering of Eg and induce red-shift of electronic bands. The torsional hindrance affects the ICT formation. The aryl groups significantly impact the thermal properties and EL ability.